Analytical Performances of Nanostructured Gold Supported on Metal Oxide Sorbents for the Determination of Gaseous Mercury - Julien Lusilao-Makiese; Emmanuel Tessier; David Amouroux; Ewa Cukrowska (International Journal of Analytical Chemistry)
Nanostructured gold supported TiO2, ZnO, and Al2O3 materials (1% w/w Au) were tested as sorbents for gaseous mercury (Hg) trapping and preconcentration. Their analytical performances were first compared with the one of traditional gold wool trap for the quantification of Hg standards injected into the argon flow followed by thermal desorption at 600°C and CVAFS detection. Good linearity and reproducibility were obtained, especially for Au/TiO2 material (R2=0.995; slope: 1.39) in the volume range of 10 to 60 µL (132–778 pg Hg). This latter even showed a better performance compared to pure Au in the volume range of 10 to 100 µL (132–1329 pg Hg) when the carrier gas flow was increased from 60 to 100 mL min-1. The method detection limit (MDL) obtained with Au/TiO2 trap (0.10 pg Hg0 L-1) was suitable for total gaseous mercury (TGM) determination. Au/TiO2 was, therefore, used in trapping and determining TGM in collected air samples. TGM values in the samples ranged from 6 to 10 ng m-3. Similar results were obtained with the commercial gold-coated sand trap which showed an average TGM concentration of 7.8±0.9 ng m-3.